Pengaruh E-Service Quality, Loyalitas Merek, Customer Value Terhadap Keputusan Pembelian Paket Berlangganan Apple Music (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Ubaidillah, Ubaidillah; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of E-Service Quality, Brand Loyalty, and Customer Value on the Purchase Decision of Apple Music subscription packages among students at the Islamic University of Malang. This research employed a quantitative method with a survey, in which data were collected through a Google Form questionnaire from 75 respondents selected using purposive sampling based on the criteria of active Apple Music users. Data analysis was conducted using multiple linear regression with SPSS 25, including validity and reliability tests, classical assumption tests, and hypothesis testing. The results show that E-Service Quality, Customer Value, and Brand Loyalty each have a positive and significant effect on purchase decisions, and simultaneously these three variables significantly influence the purchase decision of Apple Music subscription packages. These findings highlight that digital service quality, perceived value, and brand loyalty collectively play an important role in encouraging consumers to subscribe.. Keywords: E-Service Quality, Brand Loyalty, Customer Value, Purchase Decision, Apple Music.